Caracterização de produtos orgânicos da Amazônia Legal por espectroscopia Raman e cálculos ab initio - Martins, Quesle da Silva (2020)
Raman spectroscopy is worldwide consolidated technique due for its fast performance in the characterization of different materials, and which in this work was applied in the study of oils from the Amazon region. Oils of copaiba, andiroba, Brazil nuts and ostrich oil were subjected to a vibrational investigation, where ER has been the precursor technique. The choice of materials is based on being associated with the Amazonian regional socioeconomic everyday, extending beyond national borders. The potential for applicability in the natural environment of herbs and cosmetics, also stimulates a race for effective research, including the characterization stages of compounds. Infrared spectroscopy was also used in the experimental characterization process. In addition, calculations of first principles were applied, which are computational methods, which helped in the process of attribution and classification of the so-called vibrational modes. The Density Functional Theory (DFT) method was used. The techniques were able to present a spectral nature of the aforementioned samples and to identify bands related to compounds containing CH, C=C, OH and C=O groups. Among these, the symmetric stretching of the carbonyl at 1740 cm−1 and between the 1650 and 1720 cm−1 region was essential to interpret the fatty acids and their respective unsaturation.